Education in Function of Tourist Products - TAHIRI, Alberta; KOVAÇI, Idriz; KRASNIQI, Avni (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021, 2021)
In the contemporary conditions of tourism activity, tourism enterprises pay special attention to the quality of tourism production, but the dynamic development of living standards, computerized society, new computer technologies, globalization, and others, where tourism requirements and motives may change. The quality of tourism production has a different concept from that of other economic activities. Quality service in the tourism sector means meeting the requirements of the guest - tourist. In the modern conditions of tourism activity, tourism companies pay special attention and care to the quality of tourism production, but here lies the key to the success of any tourism entity, a constant effort to compete in the increasingly fierce tourism market. The need to have the highest quality tourism production forces tourism enterprises to change the managerial concept and use new techniques, putting at the center of their activities the quality of tourism production and service. The purpose of this paper is to study the impact of education on the quality of tourism products, special focus on their meaning, to formulate better strategies in quality improvement as a key element in tourism development, evaluation of tourism products and resources, and in the first place the cultural and historical ones that each particular region has at its disposal as a whole with its own tourist offer. Looking at the different geographical regions we conclude that they have their own peculiarities and different levels of tradition and level of approach to the organization of the tourism branch. But the country can on a strong foundation build the advantages and the identity of the tourism product in high quality forms and content, a product which will be competitive and complementary to the offer of the respective countries.